ANALISIS PENERAPAN MANAJEMEN KONFLIK PADA REMAJA MUSHOLLAH IMANAN BILLAH - Iftitah, Anggi Nur; Al-Hanif , Muhammad Naufal; Jannah , Miftakhul (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Conflict can occur in an organization even when its supporting components are functioning effectively because of differences in behavior among its members. Group or member conflict is a common problem that arises during organizational transitions. Conflicts related to human behavior in an organization impact its effectiveness because human resources are involved. Therefore, conflict management is expected to be able to resolve conflicts that arise. Resistance to change is the root cause of conflict. For institutions to develop and progress, conflict needs to be welcomed, handled well, and even encouraged. So an important role is needed in implementing conflict management. This research aims to provide a better understanding of how conflict management can help teenagers deal with interpersonal conflicts and improve social relations in the prayer room environment. In this research, field research methods were used with a descriptive qualitative approach used to describe the forms of words and language related to the implementation of conflict management in the case study of the teenage Muslim prayer group Imanan Billah. The research limitations contained in this research lie in the interview process, limited human resources (human resources) to ask for explanations regarding related problems are the limitations that exist in this research. The researcher realizes that there are shortcomings in starch research. Suggestions that can be given regarding this research are expected for future researchers to use more sources to find data reports needed in this research. It is hoped that the object of this research can be expanded and not limited to prayer rooms alone so that can produce better results.